Utilization of Shrimp Waste as a Raw Material in Shrimp Sauce and Its Application on Shrimp Sauce Tilapia Dishes - Shanti Dri Lestari; Mazarina Devi; Teti Setiawati (Bulletin of Culinary Art and Hospitality, 2021)
One of the innovations to increase the economic value of shrimp waste is the implementation of shrimp waste into shrimp sauce and its use in shrimp sauce tilapia dishes. The purpose of this study was to determine the protein and lead (Pb) content of shrimp waste and shrimp sauce, the degree to which shrimp sauce differed in aroma, taste, and color from commercial oyster sauce, and the degree to which panelists preferred shrimp sauce tilapia dishes via organoleptic tests. This was a two-repetition experimental study with a completely randomized design (CRD). The protein content was determined using the Kjeldahl semi-micro method, whereas the lead content was determined using the spectrophotometric method. The Duo-Trio Test was used to determine the difference in organoleptic properties between shrimp sauce and commercial oyster sauce, whereas ANOVA followed by DMRT was used to analyze the hedonic properties of shrimp sauce tilapia dishes. The results of this study indicate that shrimp waste contains 18.281 percent protein and shrimp sauce contains 6.107 percent protein. The content of lead (Pb) in shrimp waste was 0.750 mg/kg, while the content of lead (Pb) in shrimp sauce was 0.052 mg/kg. The organoleptic tests revealed that shrimp sauce had a distinct aroma, taste, and color from commercial oyster sauce, whereas the hedonic tests revealed no difference in the hedonic properties of the three dishes' aromas, but there were differences in the hedonic properties of their taste and properties. The three dishes exhibit hedonic color. Panelists preferred commercial oyster sauce tilapia dishes over shrimp sauce tilapia dishes and commercial oyster sauce mixed tilapia dishes in terms of aroma, taste, and color (1:1). The shrimp sauce formula should be refined further so that it more closely resembles commercial oyster sauce in terms of aroma, flavor, and color.